Corporeality and dance in the music of Igor Stravinsky - Steinhauer Iakovos (Muzikologija, 2023)
The high rank of Igor Stravinsky’s works (especially for ballet) prompts a discussion about the meaning of corporeality and dance in his output, a meaning that goes beyond Stravinsky’s historically-documented interest in ballet music. Thus, the encounter with Diaghilev and Nijinsky could be justified as immanently emanating from his own musical aesthetics and poetics. If dance seems for the composer to form an additional, immanent level of the music, the question of the aesthetic sense of reference to the body in Stravinsky’s music remains unanswered. By attaining a “mediated immediacy” (Helmuth Plessner) in his works, his ballet music manages to maintain a certain distance - objectifying, alienating - from subjective expression, without becoming abstract, and at the same time without losing the subjective and intersubjective bonds in which it is immersed. Through dance, Stravinsky not only strengthens the aspect of mediation in his music, but in a reflective not primitive practice, he also looks for the origins of aesthetic expression.